Transcriptomic convergence despite genomic divergence drive field cancerization in synchronous squamous tumors - Tan, Qiu Xuan; Shannon, Nicholas B.; Lim, Weng Khong; Teo, Jing Xian; Yap, Daniel R. Y.; Lek, Sze Min; Tan, Joey W. S.; Tan, Shih Jia J.; Hendrikson, Josephine; Liu, Ying; Ng, Gillian; Chong, Clara Y. L.; et al. (Frontiers in Oncology, 2024)
Field cancerization is suggested to arise from imbalanced differentiation in individual basal progenitor cells leading to clonal expansion of mutant cells that eventually replace the epithelium, although without evidence. Using deep sequencing analyses, we characterized the genomic and transcriptomic landscapes of field change in two patients with synchronous aerodigestive tract tumors. Our data support the emergence of numerous genetic alterations in cancer-associated genes but refutes the hypothesis that founder mutation(s) underpin this phenomenon. Mutational signature analysis identified defective homologous recombination as a common underlying mutational process unique to synchronous tumors. Our analyses suggest a common etiologic factor defined by mutational signatures and/or transcriptomic convergence, which could provide a therapeutic opportunity.